The hat that wore Clara B. - Turner-Denstaedt, Melanie (Farrar Straus Giroux, 2008)
In church on Mothers' Sunday when all the older ladies dress in white and wear their most beautiful hats, Clara B., sitting in the pew behind her grandmother and admiring her every move, determines to find a way to wear her grandmother's hat.